The Economics, Financing and Implementation of HIV Treatment as Prevention : What Will it Take to Get There? - Wilson, David; Taaffe, Jessica; Fraser-Hurt, Nicole; Gorgens, Marelize (Taylor and Francis, 2014)
The 2013 Lancet Commission Report, Global Health 2035, rightly pointed out that we are at a unique place in history where a “grand convergence” of health initiatives to reduce both infectious diseases, and child and maternal mortality – diseases that still plague low income countries – would yield good returns in terms of development and health outcomes. This would also be a good economic investment. Such investments would support achieving health goals of reducing under-five (U5) mortality to 16 per 1 000 live births, reducing deaths due to HIV/AIDS to 8 per 100 000 population, and reducing annual TB deaths to 4 per 100 000 population.